Multiple Symmetric Results for Quasilinear Elliptic Systems Involving Singular Potentials and Critical Sobolev Exponents in RN - Zhiying Deng; Yisheng Huang (Abstract and Applied Analysis)
This paper deals with a class of quasilinear elliptic systems involving singular potentials and critical Sobolev exponents in RN. By using the symmetric criticality principle of Palais and variational methods, we prove several existence and multiplicity results of G-symmetric solutions under certain appropriate hypotheses on the potentials and parameters.